SPECT/CT Lymphoscintigraphy Guidance Simplifies and Improves Targeted Axillary Dissection of the Clipped Nodes After Neoadjuvant Chemotherapy in Initially Node-Positive Breast Cancer. (15th November 2022) - Has Simsek, Duygu; Emiroglu, Selman; Yilmaz, Ravza; Bayram, Aysel; Isik, Emine Goknur; Tukenmez, Mustafa; Kuyumcu, Serkan; Dursun, Memduh; Muslumanoglu, Mahmut; Cabioglu, Neslihan
Abstract : Purpose: We assessed the feasibility of SPECT/CT lymphoscintigraphy ( 99m Tc-nanocolloid) method to simplify and improve targeted axillary dissection of clipped axillary lymph node (axLN) after neoadjuvant chemotherapy (NAC) in initially node-positive breast cancer. Patients and Methods: Fifteen patients who had clip placement to biopsy-confirmed axLN metastasis due to clinically node-positive breast cancer before NAC and underwent SPECT/CT lymphoscintigraphy for surgery after NAC were included into the study. SPECT/CT lymphoscintigraphy was performed to localize the clipped node and to assess if the clipped lymph node (LN) had 99m Tc-nanocolloid uptake or not. In case the clipped node had no uptake on SPECT/CT, the patient was referred to wire-guided localization procedure. Blue dye was also injected for dual mapping of sentinel LN biopsy. Results: All patients had only ipsilateral axLN metastasis. SPECT/CT lymphoscintigraphy showed that clipped LNs were radioavid in 12 of 15 patients (80%). Clipped LNs were not blue-stained in 5 patients (33.3%), and in 2 of them, clipped LNs were radioavid in SPECT/CT. Wire-guided localization was required in only 3 patients (20%) for nonradioavid/blue-stained clipped LNs. Removal of the clipped nodes was confirmed in all cases with a success rate of 100% by specimen graphy. Conclusion: SPECT/CT lymphoscintigraphy seems feasible to determine the clipped LNs intraoperatively without requiring additional invasive methods in most of the patients. This technique simplifies and improves targeted axillary dissection of the clipped axLNs after NAC in initially node-positive breast cancer and can be adapted to clinical practice with further investigations.